(untitled) (Altre Modernità, 2010)
Teresa Margolles (b. 1963) is Mexico’s foremost proponent of corpse art. Her work meditates upon her obsessions with the dead body and the processes that occur after death, and shows death as a direct result of violence. Employing a range of techniques of representation, Margolles implicates the spectator into potentially uncomfortably close contemplation of the artwork, sometimes through direct physical contact with the raw materials used in its creation. She transgresses the boundaries between the interior and the exterior of the body, and between life and death, occupying an artistic space where the minimalist and internationally accessible language of conceptual art interacts with her method of commenting upon a specifically Mexican set of circumstances, at times disguising unsettling realities behind deceptively subtle artistic techniques of representation. Drawing on theories of spectatorship and the problematics of looking at death, this essay will explore aspects of agency, eroticism and otherness in examples of Margolles’ artwork, also paying attention to the question of ethics. The bodies and body parts the artist places at the centre of her works, witness the unsettlingly direct relation between violence enacted upon the body, and its result, death. The removal of these physical entities from social space leaves behind traces and residues that now, by means of the artist’s intervention, metonymically evidence their former lives and erase the distance between dead and living bodies.